f(-49)=-5x+1

Simple and best practice solution for f(-49)=-5x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(-49)=-5x+1 equation:


Simplifying
f(-49) = -5x + 1

Reorder the terms for easier multiplication:
-49f = -5x + 1

Reorder the terms:
-49f = 1 + -5x

Solving
-49f = 1 + -5x

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by '-49'.
f = -0.02040816327 + 0.1020408163x

Simplifying
f = -0.02040816327 + 0.1020408163x

See similar equations:

| 3/4=7/x-9 | | 5x-2y+3x+y= | | -21=-9+4x | | 2x+10=5x+10-3x | | f(-2)=x^2-5 | | 8-2+a-9a= | | F(-2)=5x^2-7x+10 | | (4x+6)=(3x+9) | | (6-15)*(4+5)= | | 10x-2(x+4)=4x-7 | | 40+50m=365 | | x+x+89=180 | | 5+11p=71 | | 128=2(6y-2) | | -4x+5x=-16 | | 15+x=3*x-15 | | 12+2x=24-2x | | (45-x)/x=23 | | 47=3+11h | | b(x^2)-ab=0 | | 7x-30=205 | | 7=w-(-7)5 | | x-10=6x+4 | | 6*x+4=x-11 | | x-26=10 | | 2x-2=-4(x-4) | | 10-3*x=x+4 | | -9=6+5v | | 3y+7=5y+1 | | 32x+(-32x+25)=12 | | 142,000,000/1.19 | | 12x-20=7x+20 |

Equations solver categories